Dorsalis Pedis Free Flap: The Salvage Option following Failure of the Radial Forearm Flap in Total Lower Lip Reconstruction - Theodoros Stathas; Georgios Tsinias; Dimitra Tsiliboti; Aris Tsiros; Nicholas Mastronikolis; Panos Goumas (Case Reports in Medicine)
Reconstruction after resection of large tumors of the lower lip requires the use of free flaps in order to restore the shape and the function of the lip, with the free radial forearm flap being the most popular. In this study we describe our experience in using the dorsalis pedis free flap as a salvage option in reconstruction of total lower lip defect in a patient with an extended lower lip carcinoma after failure of the radial forearm free flap, that was initially used. The flap was integrated excellently and on the followup the patient was free of disease and fully satisfied with the aesthetic and functional result.